1995
DOI: 10.1055/s-0038-1649832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Soluble Fibrin Assay in Patients with Suspected Deep Vein Thrombosis

Abstract: SummaryBackground. The objective of this study was to determine the clinical utility of an enzyme immunoassay (HIA) for soluble fibrin in patients with clinically suspected deep vein thrombosis (DVT).Methods and Results. 101 unselected patients with clinically suspected DVT underwent blood sampling for measurement of plasma levels of soluble fibrin, and objective testing for DVT. According to results of the objective tests, patients were classified as DVT-positive (n = 34) or DVT-negative (n = 67). Using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…28 Thus, thrombin generation may occur without stimulating fibrin production, a situation previously defined as a prethrombotic state. 28 Once the thrombin inhibitory capacity is exceeded, however, soluble fibrin is formed, with increased levels noted with venous thromboembolism 29,30 and myocardial infarction. 31 In the present study, we observed a 76% increase in soluble fibrin in Values are meanϮSEM except D-dimer, which is shown as mean (25th to 75th percentile).…”
Section: Discussionmentioning
confidence: 99%
“…28 Thus, thrombin generation may occur without stimulating fibrin production, a situation previously defined as a prethrombotic state. 28 Once the thrombin inhibitory capacity is exceeded, however, soluble fibrin is formed, with increased levels noted with venous thromboembolism 29,30 and myocardial infarction. 31 In the present study, we observed a 76% increase in soluble fibrin in Values are meanϮSEM except D-dimer, which is shown as mean (25th to 75th percentile).…”
Section: Discussionmentioning
confidence: 99%
“…These methods were used in order to study the correlation between the decrease in APC ratio and changes in blood coagulation activity. The importance of increased markers of coagulation activation is uncertain but increased levels are found during thromboembolism and in patients with thrombophilia (21). Moreover decreased, dose-dependent levels are found during anticoagulant treatment (22).…”
Section: Discussionmentioning
confidence: 99%
“…The AUCs calculated for fibrin monomer (0.724 in the total patient group and 0.683 in the DVT-unlikely group) were lower than those for D-dimer tests. However, some authors have suggested that fibrin monomer tests have similar efficacy as measuring D-dimer levels in the exclusion diagnosis of venous thromboembolism [9,19,20]. The results of our study indicate the usefulness of fibrin monomer in the different logistic models containing D-dimer assays for the exclusion of DVT.…”
Section: Discussionmentioning
confidence: 49%
“…Unlike Ddimer, fibrin monomer is used to monitor the proteolytic cleavage of fibrinogen by thrombin and is therefore a marker of thrombin activity [21,22]. With regard to the difference between fibrin monomer and D-dimer, fibrin monomer reflects the early phase of DVT, whereas Ddimer reflects secondary fibrinolysis after clot formation [19]. The combined measurement of fibrin monomer as a parameter for fibrin generation and D-dimer for fibrin dissolution may provide valuable information for DVT diagnosis.…”
Section: Discussionmentioning
confidence: 99%